H2 Protects Against Lipopolysaccharide-Induced Cardiac Dysfunction via Blocking TLR4-Mediated Cytokines Expression - Tan, Sihua; Long, Zhiyuan; Hou, Xiangping; Lin, Yujie; Xu, Jingting; You, Xinchao; Wang, Tinghuai; Zhang, Yaxing (Frontiers in Pharmacology, 2019)
BACKGROUND AND PURPOSE: Septic cardiomyopathy, which is one of the features of multi-organ dysfunction in sepsis, is characterized by ventricular dilatation, reduction in ejection fraction and reduced contractility, and if severe, can lead to death. To date, there is no specific therapy exists and its treatment represents a large unmet clinical need. Herein, we investigated the effects and underlying anti-inflammatory mechanisms of hydrogen gas in the setting of lipopolysaccharide (LPS)-induced cardiomyocytes injury. EXPERIMENTAL APPROACH: Hydrogen gas was intraperitoneal injected to mice in LPS plus hydrogen group, and hydrogen group for 3 days. On 4th, LPS was given by intraperitoneal injection to mice in LPS group, and to mice in LPS plus hydrogen group. In addition, H9c2 cardiomyocytes were treated with hydrogen-rich medium for 30 min before LPS. The transthoracic echocardiography was performed at 6 hours post‐LPS to assess left ventricular end-systolic diameter (LVESD), left ventricular end-diastolic diameter (LVEDD), left ventricular ejection fraction (EF%), fractional shortening (FS%), left ventricular mass average weight (LV Mass AW), and LV Mass AW (Corrected). The histological and morphological analyses of left ventricular were performed by hematoxylin and eosin (H&E) staining, and Masson’s trichrome staining. The mRNA levels of hypertrophy marker ANP and BNP were examined by PCR in vitro. The expression of cytokines were assayed by ELISA and PCR. Moreover, western blotting was performed to examine the expression of TLR4, the activation of ERK1/2, p38, JNK, and the expression of NF-κB in nucleus after 6 hours of LPS challenge in vivo and in vitro. KEY RESULTS: LPS induced cardiac dysfunction, hydrogen therapy maintained cardiac function after LPS challenge. Furthermore, pretreatment with hydrogen resulted in cardioprotection during septic cardiomyopathy via inhibiting the expression of pro-inflammatory cytokines TNFα, IL-1β and IL-18, suppressing the phosphorylation of ERK1/2, p38 and JNK, reducing the nuclear translocation of NF-κB and LPS-induced the expression of TLR4. CONCLUSION AND IMPLICATIONS: Hydrogen therapy prevents LPS-induced cardiac dysfunction in part via downregulation of TLR4-mediated pro-inflammatory cytokines expression.